L’elettrochimica e l’idrogeno verde - Soldà, Roberto (Chimica nella Scuola, 2025)
Currently, electrochemistry is very much involved in research related to the production of green hydrogen. In this paper, to deepen some elementary knowledge of basic electrochemistry related to the production of green hydrogen, three experiments are proposed. With little time expenditure, they can be linked to the electrochemistry laboratory experiences indicated for the first two years of secondary school.